ONLINE SMES WAREHOUSE MANAGEMENT: CHALLENGES AND OPPORTUNITIES - Duaa Al-Sharif; Yosra Hamas (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
E-business faced many challenges to manage their inventory, warehouse operation and maintain their performance efficiency along with continues improvement of their customer satisfaction and experience. These challenges are increased in fruits and vegetables distribution as the difficulties in managing the storage space, maintaining inventory stocks and tracking the logistic process. This study was held to investigate the challenges that SMEs faced in the warehouse management and highlight the importance and impact of warehouse management to E-commerce for customer services and ability to deliver goods efficiently and in timely manner. This study concentrated on understanding the challenges faced by Saudi online SMEs regarded warehousing management. The study was started in Jeddah as pilot project with online small, medium enterprises (SMEs) specialized in fruits and vegetables distribution. The qualitative method was used in this study. The required data had been collected through non-participant observation and interview technique. The main core activities that had an exclusive impact on the success of E-commerce warehouse management were warehouse system, warehouse management and logistic process.